Antiviral Activity of Oral JNJ-53718678 in Healthy Adult Volunteers Challenged With Respiratory Syncytial Virus: A Placebo-Controlled Study. (19th April 2018) - Stevens, Marita; Rusch, Sarah; DeVincenzo, John; Kim, Young-In; Harrison, Lisa; Meals, Elizabeth A; Boyers, Alison; Fok-Seang, Juin; Huntjens, Dymphy; Lounis, Nacer; Mariёn, Kris; Remmerie, Bart; et al.
Abstract: Background: Respiratory syncytial virus (RSV) disease has no effective treatment. JNJ-53718678 is a fusion inhibitor with selective activity against RSV. Methods: After confirmation of RSV infection or 5 days after inoculation with RSV, participants (n = 69) were randomized to JNJ-53718678 75 mg (n = 15), 200 mg (n = 17), 500 mg (n = 18), or placebo (n = 17) orally once daily for 7 days. Antiviral effects were evaluated by assessing RSV RNA viral load (VL) area under the curve (AUC) from baseline (before the first dose) until discharge, time-to-peak VL, duration of viral shedding, clinical symptoms, and quantity of nasal secretions. Results: Mean VL AUC was lower for individuals treated with different doses of JNJ-53718678 versus placebo (203.8–253.8 vs 432.8 log10 PFUe.hour/mL). Also, mean peak VL, time to peak VL, duration of viral shedding, mean overall symptom score, and nasal secretion weight were lower in each JNJ-53718678–treated group versus placebo. No clear exposure–response relationship was observed. Three participants discontinued due to treatment-emergent adverse events of grade 2 and 1 electrocardiogram change (JNJ-53718678 75 mg and 200 mg, respectively) and grade 2 urticaria (placebo). Conclusions: JNJ-53718678 at all 3 doses substantially reduced VL and clinical disease severity, thus establishing clinical proof of concept and the compound's potential as a novel RSV treatment. Clinical trials registration: ClinicalTrials.gov: NCT02387606; EudraCT number: 2014-005041-41. Abstract : JNJ-53718678 is a respiratory syncytial virus (RSV) fusion protein inhibitor. In this proof-of-concept study, we report the antiviral activity of JNJ-53718678 (75 mg, 200 mg, and 500 mg QD for 7 days) versus placebo in healthy participants challenged with RSV.